In-vivo two-photon imaging of the honey bee antennal lobe - Haase, Albrecht (Optical Society of America, 2010)
Due to the honey bee’s importance as a simple neural model, there is a great need for new functional imaging modalities. Herein we report on the development and new findings of a combined two-photon microscope with a synchronized odor stimulus platform for in-vivo functional and morphological imaging of the honey bee’s olfactory system focusing on its primary centers, the antennal lobes (ALs). Our imaging platform allows for simultaneously obtaining both morphological measurements of the AL’s functional units, the glomeruli, and in-vivo calcium recording of their neural activities. By applying external odor stimuli to the bee’s antennae, we were able to record the characteristic glomerular odor response maps. Compared to previous works where conventional fluorescence microscopy was used, our approach has been demonstrated to offer all the advantages of multi-photon imaging, providing substantial enhancement in both spatial and temporal resolutions while minimizing photo-damages. In addition, compared to previous full-field microscopy calcium recordings, a four-fold improvement in the functional signal has been achieved. Finally, the multi-photon associated extended penetration depth allows for functional imaging of profound glomeruli.